Evidence for dark energy from the cosmic microwave background alone using the Atacama Cosmology Telescope lensing measurements. - Sherwin, B; Dunkley, J; Das, S; Appel, J; Bond, JR; Carvalho, C; Devlin, M; Dünner, R; Essinger-Hileman, T; Fowler, J; Hajian, A; Halpern, M; et al. (2011)
For the first time, measurements of the cosmic microwave background radiation (CMB) alone favor cosmologies with w = -1 dark energy over models without dark energy at a 3.2-sigma level. We demonstrate this by combining the CMB lensing deflection power spectrum from the Atacama Cosmology Telescope with temperature and polarization power spectra from the Wilkinson Microwave Anisotropy Probe. The lensing data break the geometric degeneracy of different cosmological models with similar CMB temperature power spectra. Our CMB-only measurement of the dark energy density Ω(Λ) confirms other measurements from supernovae, galaxy clusters, and baryon acoustic oscillations, and demonstrates the power of CMB lensing as a new cosmological tool.